Developing a model for the implementation of standard precautions of infection control - Nugroho, I Agung Ponco; Pujiyanto , Tri Ismu (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2025)
The prevalence of Healthcare Associated Infections (HAIs) continues to rise, posing an increased risk of morbidity and mortality. One of the key efforts to prevent and control disease transmission between patients and healthcare workers is the implementation of Standard Precautions in accordance with health protocols. This study aims to develop a model for the implementation of standard precautionary measures by nurses. This research employed a Research and Development (R&D) approach with a quasi-experimental design using a one-group pre-test and post-test model. The population consisted of nurses working in inpatient wards, selected using purposive sampling, with a total of 171 respondents. Inclusion criteria included nurses working in inpatient rooms, having over one year of work experience, and willingness to participate in the study. Data were analyzed using descriptive statistics, the Wilcoxon test, and Structural Equation Modeling (SEM) with AMOS. Results showed that the majority of participants had good knowledge (87 respondents or 50.9%), good supervision (86 respondents or 50.3%), and good management support (85 respondents or 49.7%). Factors influencing compliance with standard precautions included knowledge (p = 0.000), supervision (p = 0.000), and management support (p = 0.000). The mean compliance score before the intervention was 67.99, increasing to 74.46 after the intervention. The development of a training module was found to be effective in improving nurses’ compliance with standard precautions (p = 0.000 < 0.05). SEM analysis confirmed the significant influence of knowledge, supervision, and management support on compliance with standard precautions, with p-values < 0.05.